Sierra Leone - Public Expenditure Review - World Bank (World Bank, 2012)
When Sierra Leone emerged from its long civil war at the beginning of 2002, it had many pressing needs for recovery and reconstruction. As a consequence, Sierra Leone was one of the largest beneficiaries of foreign aid as a share of Gross Domestic Product (GDP) and aid per capita. Since then, as peace has been consolidated, the level of external assistance has gradually declined from 15.5 percent of GDP in 2002 to 5.2 percent of GDP in 2008 as donors phase out their post-conflict allocations and GDP expanded rapidly. This Public Expenditure Review (PER) records improvements in many aspects of economic and fiscal management as well as service delivery. The main message of the PER is that the Government's investment plans should be accompanied by equally ambitious improvements in sector policies, budgetary planning and execution procedures, public service reform and human resource management. Priorities include continued good macroeconomic and fiscal performance, a more effective public service, and further advances in public financial management including earlier involvement of the political leadership in budgetary decisions in the budget cycle, improvements in the public investment management system, reduced deviations in budget execution, continued procurement reform, better contract management, and deepened accountability mechanisms. These issues are reviewed and discussed below. Because of their prominence in the Second Poverty Reduction Strategy Paper (PRSP-2), the health and roads sectors are reviewed as well.